Kepemimpinan Rektor dalam Pencapaian Visi Misi Institusi di IKIP PGRI Kalimantan Timur Samarinda - Purwanto, Edi; Azainil, Azainil; Haryaka, Usfandi (Educationist: Journal of Educational and Cultural Studies, 2024)
This research aims to obtain a description of: (1) The Chancellor's leadership in achieving the vision and mission at IKIP PGRI East Kalimantan (2) The Chancellor's leadership in developing strategies at IKIP PGRI East Kalimantan (3) The Chancellor's leadership in facing obstacles to achieving and maintaining the vision and mission at IKIP PGRI East Kalimantan. Data collection techniques in this research include: 1) interviews, 2) Observation and 3) Documentation. Data processing starts from writing interviews, observations, then editing, clarifying, reducing, presenting and concluding the data. The data analysis process uses the Miles and Huberman modem which states that activities in qualitative data analysis are carried out interactively and take place continuously at each stage of the research until it is complete and the data is saturated. The results of the research show that: (1) The Chancellor's leadership has a huge influence on the achievement of the vision and mission at IKIP PGRI East Kalimantan. (2) The Chancellor's leadership in developing strategies at IKIP PGRI East Kalimantan becomes the driving force of the organization, so that it is able to organize all elements within the IKIP PGRI East Kalimantan institution. (3) The Chancellor of IKIP PGRI East Kalimantan has been equipped with experience starting from teaching lecturer, head of study program, vice chancellor, and quite a long time interacting with friends who are currently staff, making it not too difficult for him to minimize problems, manage problems and identifying problems and resolving problems (problem solving) and openness, harmonious relationships, good communication is one of the ammunition for the Chancellor of IKIP PGRI East Kalimantan to face obstacles in maintaining and realizing the vision and mission of IKIP PGRI East Kalimantan.